The fracture toughness of alumina coatings plasma-sprayed at different in situ temperatures - Xing, Ya-Zhe; Wei, Qiu-Lan; Hao, Jian-Min (Ceramics international, 2012)
Alumina coatings were prepared by atmospheric plasma spraying through controlling the surface temperature of the coatings during spraying. Both the polished and fractured cross-section microstructures of the coatings were characterized by scanning electron microscopy (SEM). The phase structures of the coatings and the feedstock were analyzed by X-ray diffraction technique (XRD). The microstructure and phase structure of the coatings prepared at different substrate temperatures were examined. SEM observations show that the intersplat bonding within the coatings was significantly improved by increasing the substrate temperature. The fracture toughness of the deposits was measured by indentation methods. For the coatings prepared at low substrate temperatures, the fracture toughness increased with the substrate temperature due to the improvement in the intersplat bonding. However, a significant decrease in the fracture toughness was found for the coatings prepared at high substrate temperatures. The change in phase structure of the coatings suggested that the residual tensile stress mainly resulted from phase transformation from γ-alumina to α-alumina at high substrate temperature should answer for the decline in the fracture toughness.